Development of Forehead Electrooculogram (EOG) Measurement Device using Plastic Optical Fibre - Kamarul Baharin, Muhammad Khaizuran; Wan Zaki, Wan Suhaimizan (Evolution in Electrical and Electronic Engineering, 2022)
This paper is carried out for the purpose of developing forehead electrooculogram (EOG) measurement to analyse and monitor the EOG signal that responds to eye movement stimulation. The corneo-retinal standing potential, which exists between the front and the rear of the human eye, can be measured using the EOG technique. Normally, pairs of surface electrodes are typically placed either above and below the eye or to the left and right of the eye which often causes discomfort to the user. Using plastic optical fibre (POF) offers many advantages with respect to the surface electrode such as high flexibility, low cost and ease to handle. This paper shows the process of detection of EOG signals which used red LED as a light source that transmitted to the skin via POF. The blinking of eye movement causes a shift in pressure, which causes a sudden rise in light intensity detected by the photodiode. The transimpedance amplifier is used to convert the photodiode current to voltage and amplify the signals. Next, the signals were connected to NodeMCU for data collection then the data were exported to the Blynk application for data analysis. Through the Internet of Things (IoT) platform, EOG signals can be analysed and monitored online by the medical practitioner and this system can be used as an online tool for EOG assessment